The new determinate pea variety ‘Meteor’ - L. I. Likhacheva; A. V. Moskalev; N. V. Likhacheva; N. N. Matolinets (Зерновое хозяйство России, 2025)
In 2009 the Krasnoufimsk Breeding Center of the Ural RIA, a branch of the FSBSI UrFARC UrO RAS, began breeding work to develop a highly productive pea variety that would be resistant to adverse environmental conditions, diseases and pests, have a non-lodging stem and non-shedding seeds. As a result of the work, there has been developed a new pea variety ‘Meteor’. The pea variety ‘Meteor’ ripens 4 days earlier than the standard variety ‘Krasnoufimsky 11’, in some years the difference can be up to 5–6 days. The plant length is 7 cm longer than that of the standard variety, with good resistance to lodging (4.6 points). The pea variety ‘Meteor’ exceeds the standard in a number of beans per plant (3.6 pcs.), in a number (12.7 pcs.) and weight of seeds per plant (2.3 g). 1000-seed weight is on average 212 g. Protein percentage is 18–26 %, while the variety ‘Meteor’ produces 26 kg more protein per hectare. Disease and moth damage of the variety ‘Meteor’ is the same or below the standard, depending on the conditions of the year. The new variety provides productivity increase of up to 29 % compared to the standard, has good drought resistance. On average, over the years of trials, the variety showed an increase to the standard by 0.18 t/ha (8 %). The variety ‘Meteor’ is highly productive, the maximum yield with 4.17 t/ha was obtained in 2022. In 2024, the new variety was included in the State List of Breeding Achievements approved for use in the Volga-Vyatka (4) and Ural (9) regions